An intricate vagina penetrating injury with a 22 cm cassava stick in situ for 6 months: a case report - Irumba, Charles; Baragaine, Justus; Obore, Susan; Haruna, Mwanje; Nteziyaremye, Julius (Journal of Medical Case Reports, 2024)
Trauma is a major cause of morbidity globally and the sixth leading cause of death at approximately 10% of all mortalities [1] and therefore a target of sustainable development goal (SDG) 11 of making cities and human settlements inclusive, safe, resilient, and sustainable [2]. There is evidence of an increase in global morbidity and mortality due to trauma. James et al. reported increasing trends of trauma cases between 1990 and 2017 from 4,260,493 injury deaths to 4,484,722 deaths in 2017 [3]. Genital urinary tract (GUT) trauma is reported in about 10% of patients presenting with trauma [4]. In a study by Ayun et al., after evaluating 21,904 patients presenting with urological emergencies, approximately 6.6% of cases were due to genitourinary trauma [5]. In Uganda, as in many Sub-Saharan African countries, the epidemiology of genitourinary trauma is not well established due to the lack of trauma registries. Most reports are extrapolated from hospital-based data and do not reflect the true incidence. However the rate of GUT is expected to rise in Africa with the increase in motor vehicle accidents, gunshot wounds from civil or domestic conflicts, and recreational activities. This may be compounded by underreporting in Africa since these injuries involve the ‘private’ parts. Genital trauma may result in external injuries to the labia, vulva or vagina, urethra, and anus and internal injuries to the bony pelvis, bladder, bowels, and reproductive organs [6]. Straddle injuries are the most common cause of genital trauma in pre-pubertal children and occur most often during bicycle riding, falls, and playing on monkey bars [7, 8]. Straddle injuries result, more often than not, as a sequelae of a child straddling an object as they fall, striking the urogenital area with the force of their body weight. In a young child with genital injury, sexual abuse should not be ignored. Additionally, accidents during recreational activities should be especially considered [6]. In a study by Corey et al. regarding the accidental genital trauma (AGT) in girls under the age of 16 years, 70.5% were straddle injuries, followed by non-straddle blunt injuries (23.5%) and penetrating injuries (6.0%). The most common sites of injury were the labia (64.0%), posterior fourchette (7.8%), and hymeneal disruption (8.4%). Encouragingly, 87.9% these were conservatively managed without further complications [9]. If not adequately managed, although they rarely cause mortality, morbidity is quite high. We present the case of a 7-year-old who had a penetrating vaginal injury by a cassava stick 22 cm in length and 2 cm in diameter that stayed in situ for 6 months. It was associated with chronic vagina pus discharge.